Pengaruh konsumsi musa paradisiaca terhadap produksi ASI pada ibu menyusui - Aprina Aprina; Adittio Rinaldi (Holistik Jurnal Kesehatan, 2020)
The effects of musa x paradisiaca flower  by lactating women on breast-milk volume and compositionBackground: Coverage of breastfeeding in Indonesia reporting by 33 provinces that 29 provinces had (88%) succeeded in achieving the 2015 as well as strategic plan target. Whereas in 2016 in Indonesia it was found that the percentage of babies getting exclusive breastfeeding up to the age of 6 months was 29.5% and babies (0-5 months) who were breastfed only 54.0%.Purpose: The effects of musa x paradisiaca flower  by lactating women on breast-milk volume and composition in the Working Area of Siring Betik Health Center, Wonosobo-Tanggamus 2019.Method: A quantitative study by quasi experimental with One group pretest - posttest. The population was 34 respondent, the statistical test used the dependent t-test. The lacation at Siring Betik Health Center, Wonosobo -TanggamusResults: The results of statistical tests using dependent tests obtained p-values of 0,000 (α <0.05). There is an influence of  Musa x paradisiaca flower  by lactating women on breast-milk volume and composition.Conclusion: This research can be used as a guide to provide counseling about the provision of musa x paradisiaca flower  as a non-pharmacological alternative for lactating women. It is inexpesive and finding in  tropical country such as Indonesia.Keywords : Musa x paradisiaca flower; Lactating women; Breast-milk volume; CompositionPendahuluan: Cakupan pemberian ASI di Indonesia dari 33 provinsi yang melapor, sebanyak 29 di antaranya (88%) berhasil mencapai target renstra 2015. Sedangkan Pada tahun 2016  di Indonesia diketahui bahwa jumlah persentase bayi mendapat ASI eksklusif sampai usia 6 bulan sebesar 29,5% dan bayi yang mendapat ASI usia 0-5 bulan sebesar 54 ,0%.Tujuan: Diketahui pengaruh konsumsi Musa Paradisiaca terhadap produksi ASI ibu menyusui di Wilayah Kerja Puskesmas Siring Betik Kec. Wonosobo Kab. Tanggamus Tahun 2019.Metode: Penelitian Kuantitatif dengan metode Quasi Eksperimental dengan pendekatan One group pretest – posttest. Populasi sebanyak 34 responden, sampe yang digunakan adalah ibu  menyusui, uji statistik menggunakan uji t-tes dependen. Lokasi  di Wilayah Kerja Puskesmas Siring Betik Kec. Wonosobo Kab. TanggamusHasil: Didapat nilai p-value  0.000 (α<0.05). Terdapat pengaruh konsumsi musa paradisiaca terhadap produksi ASI ibu menyusuiSimpulan: Diharapkan penelitian ini dapat dijadikan panduan untuk memberikan penyuluhan tentang pemberian pemberian sayur jantung pisang sebagai alternatif non farmakologi memperlancar ASI kepada ibu menyusui, selain ekonomis dan bahanya mudah didapat